THE HISTORY AND IMPORTANCE OF AL-AHRAM AND AL-AKHBAR IN ARAB MEDIAAND THE LINGUISTIC FEATURES OF THE CLAUSE SENTENCES OF THE ARABIC ARTICLES - Boburmirzo Mahkamboyev (Bright Mind Publishing, 2025)
This article explores the historical significance and continuing importance of Al-Ahram and Al-Akhbar newspapers within the landscape of Arab media. It examines their evolution, influence, and role in shaping public discourse. Furthermore, the study analyzes the linguistic features of clause sentences found in their Arabic articles, potentially focusing on syntax, style, and their impact on readability and persuasive power.
Keywords: Al-Ahram, Al-Akhbar, Arab media, history, linguistics, clause structures, Arabic language, journalism.